The effects of supplementing growing finishing swine diets with betaine and (or) choline on growth and carcass characteristics - J W Smith II; B T Richert; K Q Owen; J R Bergstrom; S A Blum; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1994)
Eighty crossbred gilts (initially 134 lb) were used in a growth assay to evaluate the effects of supplementing finishing pig diets with betaine and (or) choline on growth performance and carcass characteristics. Betaine at 0 or 1000 ppm and choline at 0 or 100 ppm were used in a 2 x 2 factorial arrangement in eight randomized complete blocks. A fifth treatment, 1000 ppm betaine from a liquid, 16 carbon betaine (Lonzaine 16, distributed by Lonza, lnc., Fair Lawn, NJ), was added to further evaluate the efficacy of another form of betaine. Pigs were blocked by weight and ancestry and allotted to one of the five dietary treatments. The corn-soybean meal based experimental diets were formulated to .75% lysine, .65% Ca, and .55% P. Pigs fed the diet supplemented with betaine had higher ADG than pigs fed the control diet. The pigs fed the diet with added choline had poorer feed efficiencies and lower growth rates than pigs fed the other diets. When pigs were slaughtered at 230 lb, the pigs fed the diet with added betaine tended to have larger loin muscle areas (LMA) than the pigs fed the control diet. In conclusion, further research into the mechanisms of betaine use is needed because of the different responses that betaine has elicited in various research trials. The cost of betaine must be low enough to reap the benefits of supplementing betaine in finishing swine diets.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Betaine; Choline; Pigs; Finishing